Origami microfluidics for radiant cooling with small temperature differences in buildings. (1st November 2020) - Grinham, Jonathan; Craig, Salmaan; Ingber, Donald E.; Bechthold, Martin
Highlights: A novel radiant cooling technology is described. The technology consists of a foldable surface with integrated microfluidics. The thermal performance is characterized as a function of the surface folding angle. Experiments confirm increased rates of heat transfer and cooling. The technology may help reduce the lifecycle emissions of HVAC installations. Abstract: Design and fabrication methods translated from microfluidics, microelectromechanical systems, origami, and biologically inspired engineering may offer efficiency improvements for water-based thermoregulation in buildings. This paper introduces foldable radiant cooling devices that are fabricated by lamination with integrated microfluidic water-circuits. These devices produce more surface convection because of their geometry and because they have more surface area than flat panels. As a result, lukewarm water instead of chilled water may be sufficient for cooling a room, leading to potential savings in primary energy use and lifecycle greenhouse gas emissions. Analytical models and physical experiments show a 55–67% improvement in thermal performance when comparing these novel folded surfaces to flat surfaces, mainly due to the improved convection heat transfer.